Pengaruh Penggunaan Pupuk Organik Hayati terhadap Sifat Fisika Tanah di Kecamatan Pare Kabupaten Kediri - Tiurma Wiliana Susanti Panjaitan, Gatot Sargiman (AGROKNOW, 2013)
Abstract. This research aims to return soil fertility level passes soil quality repair process with biological organic fertilizer (POH) use, so that increase result and agro product quality. Watchfulness activity about biological organic fertilizer is done at village Pelem, Pare (Kediri) with location without use POH and use POH between 1 up to 7 year. soil sample taking appointeds at random and done several analysis, that is soil physics, pregnancy pOh both for still new (4 day) and that sufficiently long days (1 month). Data is analyzed with analysis of variance and to detect difference between treatments is done test LSD in standard 5%. .Â The research got several conclusions, that is (1) biological organic fertilizer (POH) that stills new (fermentation during 4 days) not yet give stable organic ingredient result. But such biological organic fertilizer can direct be used for organic ingredient increase in soil although the result less optimal. biological organic fertilizer best memfermentasikan during around 1 month; (2) biological organic fertilizer increasing into soil as much as 2 ton/ha to every planting will give optimal organic ingredient pregnancy since gift during 7 year; (3) biological organic fertilizer use consequence soil physics character repair in general influential manifestly since use in the year second. Maximum wide capacity magnitude that reachable around 44%.Kata Kunci : Pupuk Organik Hayati (POH), Sifat Fisik Tanah.